Comparative numerical analysis of heat and mass transfer characteristics in Sisko Al2O3-EG and TiO2-EG fluids on a stretched surface - Jyothi, K.; Dasore, Abhishek; Ganapati, R.; Shareef, Sk. Mohammad; Chamkha, Ali J.; Prasad, V. Raghavendra (Tech Science Press, 2024)
In the current research, a thorough examination unfolds concerning the attributes of magnetohydrodynamic (MHD) boundary layer flow and heat transfer inherent to nanoliquids derived from Sisko Al2 O3-Eg and TiO2-Eg compositions. Such nanoliquids are subjected to an extending surface. Consideration is duly given to slip boundary conditions, as well as the effects stemming from variable viscosity and variable thermal conductivity. The analytical approach applied involves the application of suitable similarity transformations. These conversions serve to transform the initial set of complex nonlinear partial differential equations into a more manageable assembly of ordinary differential equations. Through the utilization of the FEM, these reformulated equations are solved, considering the specified boundary conditions. The outcomes attained are graphically depicted by means of plots and tables. These visual aids facilitate a comprehensive exploration of how diverse parameters exert influence over the distributions of velocity, temperature, and concentration. Furthermore, detailed scrutiny is directed towards the fluctuations characterizing pivotal parameters, viz., Nusselt number, skin-friction coefficient, and Sherwood number. It is identified that the Nusselt number showcases a diminishing trend coinciding with increasing values of the volume fraction parameter (φ). This trend remains consistent regardless of whether the nanoliquid under consideration is Al2O3-Eg or TiO2-Eg based. In contrast, both the skin-friction coefficient and Sherwood number assume lower values as the volume fraction parameter (φ) escalates. This pattern remains congruent across both classifications of nanoliquids. The findings of the study impart valuable insights into the complex interplay governing the characteristics of HMT pertaining to Sisko Al2 O3-Eg and TiO2-Eg nanoliquids along an extending surface. © 2024, Tech Science Press. All rights reserved.